FOREIGN LANGUAGE TEACHING IN SPECIAL DIRECTIONS - Erkinov Adham Anvar o‘g‘li; Abdullayeva Zarina; Abdullayeva Zarina (TADQIQOTLAR, 2026)
Annotation. This article examines the methodologies and importance of teaching foreign languages within special directions, focusing on English for Specific Purposes (ESP). Traditional language instruction often fails to address the unique communicative needs of specialized professional fields. This paper analyzes how integrating student-centered strategies—such as needs analysis, task-based learning, and authentic materials—enhances professional linguistic competence and student motivation.